Analyzing Passenger Car Equivalent for Motorcycle on Mixed Traffic Flows in Denpasar City during the COVID-19 Pandemic - Kariyana, I Made; Aryastana, Putu; Sumarda, Gede; Indramanik, I B; Wahyuni, Ni Wayan (International Journal of Engineering and Emerging Technology, 2020)
Passenger Car Equivalent (PCE) is the conversion factor of various vehicle types into passenger car units. Characteristics and geometric road conditions affect the PCE value. The PCE value on urban roads has been determined in the Indonesian Highway Capacity Manual (IHCM) in 1997. Previous studies show that the PCE value for motorcycles according to IHCM isn‘t appropriate. The COVID-19 outbreak that occurs at Denpasar in early March 2020 led to a policy to restrict community activities outside the home, affects the traffic flow conditions in Denpasar City. The study's aim is to estimate the PCE value for the motorcycle at COVID-19 pandemic on mixed traffic flows in Denpasar and compare it with the PCE value in the IHCM. The PCE value is determined using the time headway method. The analysis results show the PCE value of the motorcycle during the COVID-19 pandemic was different from the PCE value of the IHCM.